Exogenous Zinc Application and Generative Traits of Three Local Shallot Varieties - Remi Widana Putri; Elkawakib Syam'un; Fachirah Ulfa (HAYATI Journal of Biosciences, 2024)
Increasing shallot (Allium ascalonicum L.) production can be done by application of botanical or true shallot seeds (TSS). Meanwhile, it is well understood that botanical seeds are difficult to produce due to shallots' low flowering capacity. This study aimed to evaluate the generative traits of three local shallot varieties affected by various doses of zinc (Zn). This study was structured using a split-plot design, where the main plots were varieties (Lokana, Rubaru, and Ambassador 3 Agrihorti). In addition, the sub-plot treatment, the dose of zinc (0, 0.5, 1, and 1.5 kg ha-1), was repeated three times. There is an effect of the main factor (variety) where Rubaru and Ambassador 3 Agrihorti show the fastest umbel emergence. In addition, our data show the interaction effects on the age of sheat breaking, flower blooming (DAP), morphology traits of generative organs, and leaf traits. In detail, Lokana with a Zn dose of 1.5 ha-1 shows the best results on the length and diameter of the umbel stalk; Rubaru with Zn 1 kg ha-1 on the age of broken sheath and chlorophyll index; and the Ambassador 3 Agrihorti with Zn 0.5 kg ha-1 on the number of flowers. On the one hand, it can be concluded that each variety responded differently to the dose of Zn. Concerning seed production, on the other hand, the Ambassador 3 Agrihorti with Zn 0.5 kg ha-1 has better potential to be developed for TSS, as seen from the number of flowers per umbel, a higher percentage of flowering plants and a relatively fast flowering time than other varieties.